PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP EMPATI SISWA KELAS VI SD NEGERI 54 BANDA ACEH - Fariha Mutiara Ramadhani; Linda Vitoria; Mislinawati (STKIP Subang, 2026)
This reseacrh was motivated by the increasing use of social media among elementary school students, which has the potential to influence their socio- emotional development, particularly empathy. The study employed a quantitative approach with a causal-associative research design. The population consisted of 96 sixth-grade students from SD Negeri 54 Banda Aceh, all of whom were included in the sample using a total sampling technique. The study aimed to determine the influence of social media usage on the empathy of these sixth-grade students. Data were collected using a social media usage questionnaire and an empathy questionnaire. The data were analyzed using normality tests, linearity tests, Spearman Rank correlation tests, simple linear regression, and significance tests (F-test) with the aid of SPSS version 31 software. The results indicated a significant influence of social media usage on the empathy of the sixth-grade students at SD Negeri 54 Banda Aceh. The Spearman Rank correlation test yielded a value of - 0.410 with a significance level of < 0.001, indicating a significant negative relationship of moderate strength. Simple linear regression analysis showed a regression coefficient of -0.882, with the equation Y = 159.725 – 0.882X and a significance level of < 0.001. The F-test results showed an F-calculated value of 39.451, which was greater than the F-table value of 3.94 (39.451 > 3.94), with a significance level of 0.001 < 0.05. The coefficient of determination (R-squared) of 0.296 indicated that social media usage contributed 29.6% to student empathy, while 70.4% was influenced by factors outside the scope of this study. It is concluded that social media usage has a significant negative influence on the empathy of sixth- grade students at SD Negeri 54 Banda Aceh.